Answer:

General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
<u>Algebra I</u>
- Terms/Coefficients
- Factoring
<u>Algebra II</u>
- Exponential Rule [Powering]:

- Solving exponential equations
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
<em />
<em />
<em />
<u>Step 2: Solve for </u><em><u>x</u></em>
- Rewrite:

- Set:

- Factor:

- [Division Property of Equality] Divide 3 on both sides:

- [Subtraction Property of Equality] Subtract 3x on both sides:

- [Subtraction Property of Equality] Subtract 6 on both sides:

- [Division Property of Equality] Divide -1 on both sides:

Answer:
(12.2,-6.4)
Step-by-step explanation:
The results from Desmos are as shown.
The displayed values are (12.294, -6.353)
Answer:
x = - 4 y = - 4
Step-by-step explanation:
x+y= - 8
-9x-6y=60
First, solve for x in the first equation:
x+y = - 8 Subtract y from both sides
x + y - y = -8 - y y cancels on the left
x = - 8 - y
Now plug in what you found for x into the 2nd equation and solve for y.
- 9x - 6y = 60
-9(- 8 - y) - 6y = 60 Multiply out
72 + 9y - 6y = 60
72 + 3y = 60 Subtract 72 from both sides
72 - 72 + 3y = 60 - 72 72 cancels on the left
3y = - 12 Divie both sides by 3
3y/3 = -12/3 3 cancels on the left because 3/3 = 1
y = -4
Now plug your answer for y back into the first equation to get x.
x + y = -8
x + (-4) = - 8 Add 4 to each side
x - 4 + 4 = - 8 + 4 4 cancels on the left
x = -4
x = - 4 and y = - 4
Answer:
Vertical stretch by a factor of 6
Step-by-step explanation:
Multiplying the function value by a constant moves its y-coordinate farther away from the x-axis by that factor. It causes a vertical stretch. Here, ...
the vertical stretch factor is 6